Pembinaan Prestasi Cabang Olahraga Hoki di Kabupaten Demak Tahun 2022 - Sari, Ayu Novita; Irsyada, Roas (Universitas Negeri Semarang, 2023)
The purpose of this study was to find out the process of fostering achievements in hockey sports in Demak Regency regarding the organization, coaches, athletes, training programs, facilities and infrastructure, and achievements that have been obtained. Researchers in carrying out research on fostering hockey sports achievement in Demak Regency used a descriptive qualitative research method using three research instruments namely observation, interviews, and documentation. The stages of achievement development in Demak Regency hockey have gone well. By having human resources ranging from athletes, coaches, to administrators. Have an exercise program. Have an organizational structure. Have infrastructure. And the funding that has been obtained from KONI grants and also contributions from athletes. Based on the results of the study, the researchers gave suggestions, the Demak Regency hockey management to add coaches for goalkeepers and also physical trainers, so that each athlete gets maximum guidance for the development of the achievements of each athlete. The conclusion from this study is that hockey in Demak Regency has human resources ranging from qualified trainers, athletes and administrators, has a permanent source of funds, namely from KONI grants and also has proper facilities and infrastructure used to play and also compete